The Effect of Kaizen Culture and Work Competency on Employees Performance in PT. Bank Sumut Air Joman Branch - Rahmat Putra Ahmad Hasibuan (Proceedings of AICS - Social Sciences, 2017)
The objective of this study is to investigate the effect of kaizen culture and work competency on employees’ performance in PT. Bank Sumut Air Joman Branch. The Data are obtained by conducting interview and questionnaire. The data is processed by applying multiple linear regression analysis. The Findings Indicated there is positive effect of kaizen culture and work competency on employees’ performance in PT. Bank Sumut Air Joman Branch. This Implies that Kaizen culture and work competency affect employees’ performance.